Upaya Preventif Pencegahan Korupsi melalui Edukasi Penanaman Nilai Integritas Di Desa Bulusulur - Ruslina Dwi Wahyuni; Titik Vitriani (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
This study aims to describe efforts to implement socialization and education on the cultivation of integrity values from an early age through the Al Barokah Qur'an Education Park (TPQ). The subjects in this study were TPQ Al Barokah students. The method used in writing this article is a literature search related to efforts to integrate integrity values in TPQ Al Barokah learning. This research uses qualitative descriptive analysis research methods, with the hope that the data obtained can be comprehensive and in-depth. Some of the steps taken include collecting literature, reading and recording then comparing literature to be processed and producing conclusions.The data used is secondary data derived from textbooks, journals, scientific articles, literature reviews containing the concepts studied. The results of the research obtained are Efforts to instill integrity values from an early age at TPQ Al Barokah are very useful for adding knowledge, insight into changing patterns of piker and forming good character in students to apply integrity values.